Impact of Paraphrasing Strategy on Mathematical Problem-Solving Skills and Performance: Exploring Their Interrelationship - Delideli, Jay (Journal of Interdisciplinary Perspectives, 2024)
This quasi-experimental study was conducted to determine the impact of paraphrasing strategy on the mathematical problem-solving skills and mathematics performance of first-year college students while also exploring the interrelationship between these skills and performance. The 40 participants of this study were randomly assigned into the experimental and control groups following the pre-test and post-test equivalent group design. The instruments used were the Mathematical Problem-Solving Skills Inventory by Chirinda (2013) and a researcher-made performance test. Statistical analyses were the independent sample t-test, paired sample t-test, and Pearson r. The experimental group was taught using a paraphrasing strategy, while the control group was taught using the traditional method. According to the findings, there is a statistically significant difference between the post-test scores of the experimental and control groups, with the experimental group scoring higher. Even though both groups improved in their post-test, the significant difference in the mean gain scores shows that the experimental group performed better than the control group, and this improvement was due to the use of a paraphrasing strategy. A significant correlation also existed between mathematical problem-solving skills and mathematics performance, implying that as the mathematical problem-solving skill increases, performance increases. Theoretically, these findings support the cognitive learning theory, which emphasizes the importance of active engagement strategies like paraphrasing in enhancing understanding and retention. This study suggests that educators should incorporate paraphrasing strategies into their teaching methods to improve students' mathematical performance. It can be concluded that a paraphrasing strategy can be used to increase performance in Mathematics. Further research is recommended to explore the long-term effects of paraphrasing strategy on different student populations.